Pengaruh Waterfront Terhadap Kondisi Lingkungan Sosial Kelurahan Benua Melayu Laut - Nana Novita Pratiwi (Jurnal Teknologi Lingkungan Lahan Basah, 2021)
Waterfront is a concept to support the availability of open spaces in Pontianak City. Besides functioning ecologically, Waterfront can also function aesthetically and economically so that its existence affects the social environment. One of the most popular Waterfront locations for visitors is the Waterfront  in Benua Melayu Laut Ubran Village. The study aims to determine the effect of the Waterfront on the conditions of the social environment in Benua Melayu Laut Urban Village. The analysis used is the frequency distribution and composite index. The results showed that the effect of Waterfront on social environmental conditions was high with an index value of 3.01. This influence can be in the form of a positive or negative influence. Positive influences include increased public awareness of the social environment, increased sense of responsibility in maintaining environmental quality, a high sense of care among fellow citizens and increased cooperation in improving environmental quality and aesthetics. The magnitude of this positive influence can have implications for the comfort and safety of the social environment. Meanwhile, the negative effects that can occur are high conflicts and unfair competition which have an effect on the decline in the social security of the Waterfront Benua Melayu Laut.